2021
DOI: 10.3389/fphy.2021.675375
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Currents and Magnetic Fields in H2+ Induced by Coherent Resonant Bichromatic Circularly Polarized Laser Pulses: Effects of Orientation, Phase, and Helicity

Abstract: We theoretically study pulse phase and helicity effects on ultrafast magnetic field generation in intense bichromatic circularly polarized laser fields. Simulations are performed on the aligned molecular ion H2+ from numerical solutions of corresponding time-dependent Schrödinger equations. We demonstrate how electron coherent resonant excitation influences the phase and helicity of the optically induced magnetic field generation. The dependence of the generated magnetic field on the pulse phase arises from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…( 6) can be simplified to [note that the time-dependent term (1/c)∂ 𝑗 (𝑟,t) /∂t in Eq. ( 6) is usually found to be negligible [23,25,33] ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 6) can be simplified to [note that the time-dependent term (1/c)∂ 𝑗 (𝑟,t) /∂t in Eq. ( 6) is usually found to be negligible [23,25,33] ]…”
Section: Resultsmentioning
confidence: 99%
“…Actually, for resonance excitation, the excited state transition probability is determined by the intrinsic transition dipole of molecules and the electric field strength and is insensitive to the pulse phase. [23]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakthrough of laser pulses [1][2][3][4] ranging from the subfemtosecond toward the attosecond time domain has opened a new door for investigating atomic and molecular dynamics on ultra-short time scales [5][6][7][8][9]. Recently, it has been reported that electronic currents and magnetic fields can be effectively induced by attosecond UV pulses in molecules [10,11]. Such light-induced ultrashort magnetic pulses have shown potential applications in many fields, such as molecular paramagnetic bonding [12], demagnetization processes [13] and magnetic data recording [14].…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of optical angular momentum (AM) has been proposed in the last few decades as an effective tool to achieve optical manipulation, quantum communication and so on [1,2]. Generally, there are two kinds of AM carried by light, spin AM (SAM) and orbital AM (OAM).…”
Section: Introductionmentioning
confidence: 99%